Determinants of cholesterol efflux capacity in humans. (January 2018) - Talbot, Charlotte P.J.; Plat, Jogchum; Ritsch, Andreas; Mensink, Ronald P.
Abstract: High-density lipoproteins (HDL) play an important role in the reverse cholesterol transport (RCT) pathway, contributing to the efflux of excess cellular cholesterol. However, the classic hypothesis that raising HDL-cholesterol (HDL-C) concentrations reduces cardiovascular disease (CVD) risk has been challenged by recent intervention studies. Nowadays, improving cholesterol efflux capacity of HDL particles is considered to be a better target for the prevention of CVD. We will first briefly summarize assays that have been developed in order to quantify HDL-mediated cholesterol efflux from macrophages. However, the main purpose of this review is to discuss factors and ABC-transporters that are associated with HDL-mediated cholesterol efflux, such as HDL particle characteristics (i.e. HDL size and composition), subjects' characteristics (i.e. gender, BMI and age), HDL-C raising drugs, lifestyle, genetic background, as well as acute and low-grade systemic inflammation. Results suggested that factors associated with small HDL particles efficiently promote cholesterol efflux via the ABCA1 transporter. This appears to contradict findings from epidemiological studies suggesting that in particular large HDL2 particles are related to a reduced CVD risk. It is therefore essential not only to understand targets to increase cholesterol efflux capacity, but also to prove causality between cholesterol efflux capacity and the prevention of CVD risk.